The Effects of High Stakes Testing in an Inner-City Elementary School: The Curriculum, the Teachers, and the English Language Learners - Wayne E. Wright (Arizona State University, 2015)
Drawing on interviews with teachers, this study examines the effects of a high-stakes standardized test (the SAT-9), on a large inner-city elementary school in southern California with a high English Language Learner (ELL) student population. Specifically, the study addresses the following questions: (a) How much of an emphasis is there on the SAT-9? (b) Do teachers believe the SAT-9 is a fair and valid measure of teaching and student learning? (c) How has the SAT-9 affected the curriculum taught to students, especially ELL students? (d) How has the SAT-9 affected the teachers and students? And, (e) has the SAT-9 improved teaching and learning at the school under study? The findings reveal that standardized testing has not resulted in higher quality teaching and learning in this school; rather, it has resulted in a narrowed curriculum and harmful effects on both teachers and students.